A função indeterminadora de anúncios com o clítico se : uma leitura de construção - Silva, Alexsandra Ferreira da (2009)
In this research we have worked with structures formed by verb + SE, commonly found in pieces of advertisement. Based on a linguistic functionalism theory, in which linguistic structures are studied in their real context of usage, we have tried to carry a study of these structures within a textual genre so as to analyze what motivates this type of construction. Having in mind the hypothesis that the structure V (singular) + SE is connected to a fixed construction that constitutes to a communicative model of such genre. Besides this we have also worked under the construction grammar s perspective emphasizing the existence of a compositional meaning which is related to the structure V + SE + SN. This meaning would be present in users subjective knowledge which relies on acquired experience through social interaction. We believe that the communicative intention is to highlight the kind of service being offered in these advertisements without paying much attention to the ones who are actually advertising. Trying to better understand these issues, we have carried out field research through the study of pieces of advertisement created by high school students. Not only have we verified the recurrent use of the construction V + SE, but also the way in which students make use of them in this context. The initial intention was to analyze if schooling was significantly contributing to foster the use above mentioned structure in accordance with the indetermination and passive canonic formulae taught at this institution. The results of all this process have revealed that the formulae V (singular) + SE constitutes a type of fixed construction in a genre that selects arguments in a pragmatic way. Besides that, we realized that this type of construction, not withstanding verb predication, fulfills to the sole communicative goal of highlighting the action embedded in the verb, defocusing its agent. To put it in other words, showing a usage quite ordinary and predictable, which has been attaining the status of a stable grammatical construction making evident a grammaticalization process.